The Protection of the Integrity of Electronic Records: An Overview of the UBC-MAS Research Project - Duranti, Luciana; MacNeil, Heather (Archivaria, 1996)
The research project currently underway at the University of British Columbia’s Master of Archival Studies Programme is directed toward identifying and defining the requirements for creating, handling, and preserving reliable and authentic electronic records. This article provides an overview of the research project, outlining its objectives and methodology, summarizing its conceptual analysis, and presenting its major findings to date. RÉSUMÉ Le projet de recherche en cours au Programme de maîtrise en études archivistiques de l’Université de la Colombie-britannique vise à identifier et à définir les conditions requises pour la création, la manipulation et la sauvegarde de documents informatiques sûrs et authentiques. Cet article brosse un tableau du projet de recherche en soulignant ses objectifs et sa méthodologie, en résumant son analyse conceptuelle et en présentant ses principales conclusions.